Rare bird documentation form for Northern Goshawk at Sunken Grove, 1980 - Jardine, Wallace E.et al (1980)
Rare bird documentation form for two Northern Goshawks at Sunken Grove at Pocahontas County, IA on September 6, 1980. Epson - sheet feed